Understanding the Context for Incorporating Equity into Quality Improvement Throughout a National Health Care System - Collaboration group (Mary Ann Liebert, 2023)
Purpose: Although health care systems aspire to deliver equitable care, practical tools that empower the health care workforce to weave equity throughout quality improvement (QI) processes are lacking. In this article, we report findings from context of use interviews that informed the development of a user-centered tool to support equity-focused QI. Methods: Semistructured interviews were conducted from February to April of 2019. Participants included 14 medical center administrators, departmental or service line leaders, and clinical staff involved in direct patient care from three Veterans Affairs (VA) Medical Centers within a single region. Interviews covered existing practices for monitoring health care quality (i.e., priorities, tasks, workflow, and resources) and explored how equity data might fit into current processes. Themes extracted through rapid qualitative analysis were used to draft initial functional requirements for a tool to support equity-focused QI. Results: Although the potential value of examining disparities in health care quality was clearly recognized, the data necessary for examining disparities were lacking for most quality measures. Interviewees also desired guidance on how inequities could be addressed through QI. The ways in which QI initiatives were selected, carried out, and supported also had important design implications for tools to support equity-focused QI. Discussion: The themes identified in this work guided the development of a national VA Primary Care Equity Dashboard to support equity-focused QI within VA. Understanding the ways in which QI was carried out across multiple levels of the organization provided a successful foundation upon which to build functional tools to support thoughtful engagement around equity in clinical settings.